Simulation, Optimization and Thermodynamic, Economic and Environmental Analysis of Cryogenic Cycle, Dew Point Regulation in an Existing Refinery - Ehsanolah Assareh; Mojtaba Nedaei; Sajjad Keykhah (Advances in Engineering and Intelligence Systems)
Energy is one of the critical parameters for sustainable development in any nation. Technology progress and lifestyle change have led to increased energy demand. In this paper, an optimal structure for thermodynamic, environmental and economic improvement of the existing dew point adjustment unit (South Pars Energy Zone in Iran) is presented. Also, the analysis of the sensitivity of the turbo-expander outlet pressure on the total exergy efficiency, duty reboiler of gas-liquid distillation towers and the intensity of NGL product production in the current and optimal state has been performed. The current and optimal process is simulated by using Aspen Hysys software. The optimal structure used the low temperature of the waste gas to condense the vapors above the propane and butane towers, and by removing the air conditioners leads to energy recovery, increase in overall exergy efficiency and reduce in carbon dioxide emissions and NGL production costs. The optimization scenario showed that the total exergy efficiency increased to 0.7305 and the total exergy loss decreased by 23.22%. In the environmental sector, the optimal process resulted in a 39% reduction in carbon dioxide footprint, and economically, with annual savings of 3107549.45 $ in energy supply costs, it resulted in 11.54T reduction in NGL value production costs.